Caspase‐8‐driven apoptotic and pyroptotic crosstalk causes cell death and IL‐1β release in X‐linked inhibitor of apoptosis (XIAP) deficiency. (17th January 2023) - Hughes, Sebastian A; Lin, Meng; Weir, Ashley; Huang, Bing; Xiong, Liya; Chua, Ngee Kiat; Pang, Jiyi; Santavanond, Jascinta P; Tixeira, Rochelle; Doerflinger, Marcel; Deng, Yexuan; Yu, Chien‐Hsiung; et al.
Abstract: Genetic lesions in X‐linked inhibitor of apoptosis (XIAP) pre‐dispose humans to cell death–associated inflammatory diseases, although the underlying mechanisms remain unclear. Here, we report that two patients with XIAP deficiency–associated inflammatory bowel disease display increased inflammatory IL‐1β maturation as well as cell death–associated caspase‐8 and Gasdermin D (GSDMD) processing in diseased tissue, which is reduced upon patient treatment. Loss of XIAP leads to caspase‐8‐driven cell death and bioactive IL‐1β release that is only abrogated by combined deletion of the apoptotic and pyroptotic cell death machinery. Namely, extrinsic apoptotic caspase‐8 promotes pyroptotic GSDMD processing that kills macrophages lacking both inflammasome and apoptosis signalling components (caspase‐1, ‐3, ‐7, ‐11 and BID), while caspase‐8 can still cause cell death in the absence of both GSDMD and GSDME when caspase‐3 and caspase‐7 are present. Neither caspase‐3 and caspase‐7‐mediated activation of the pannexin‐1 channel, or GSDMD loss, prevented NLRP3 inflammasome assembly and consequent caspase‐1 and IL‐1β maturation downstream of XIAP inhibition and caspase‐8 activation, even though the pannexin‐1 channel was required for NLRP3 triggering upon mitochondrial apoptosis. These findings uncouple the mechanisms of cell death and NLRP3 activation resulting from extrinsic and intrinsic apoptosis signalling, reveal how XIAP loss can co‐opt dual cell death programs, and uncover strategies for targeting the cell death and inflammatory pathways that result from XIAP deficiency. Synopsis: XIAP deficiency causes hemophagocytic lymphohistiocytosis and Crohn's disease. Analysis of XIAP‐deficient patients and cellular studies show that apoptotic caspases and GSDMD act redundantly downstream of caspase‐8 to cause excess cell death and IL‐1β release. XIAP deficiency increases cleaved caspase‐8 and GSDMD in mucosal tissue and cells Crosstalk in apoptosis and pyroptosis sensitises cells to caspase‐8‐driven death and IL‐1β activation upon XIAP inhibition Pannexin‐1 and GSDMD are dispensable for NLRP3 inflammasome formation downstream of caspase‐8 Pannexin‐1 cleavage by caspase‐3 and caspase‐7 is required for efficient NLRP3 activation following intrinsic apoptosis Abstract : Loss of XIAP leads to the activation of multiple cell death pathways to promote inflammatory diseases.